ANALISIS KEMAMPUAN EKONOMI RUMAH TANGGA PETANI KARET DI SUMATERA SELATAN - Hendro, Omar; Mulyana, Andy (Universitas muhammadiyah palembang, 2012)
Issue of this research is: (1) There is factors influence applied to forming of capital for rejuvenation of rubber plantation, (2) Does farmer have allocation ability of the earnings to forming of capital for rejuvenation of rubber plantation, (3) Does the residue of earnings that is not consumed (real saving) can be applied to forming of capital for rejuvenation of rubber plantation, (4) Is there is source of other business to add earnings of farmer to forming of capital for rejuvenation of rubber plantation. Analytical method used is regression and hypothesis test. The result of this research is: (1) Partially, household earning, residue of earnings that is not consumed (real saving), formal education of farmer, old worked as farmer, and rubber plantation wide variable have positive and significance effects to forming of capital for rejuvenation of rubber plantation, (2) Partially, household expenditure variable have negative and significance effects for forming of capital to forming of capital for rejuvenation of rubber plantation, and (3) Partially, sum of member of adult families and ownership status of rubber plantation variable have no significance effects to forming of capital for rejuvenation of rubber plantation.